ELEMENTARY CLASSIFICATION OF QUASI-BOOLEAN ALGEBRAS - Budaghyan, L. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
An algebra is called a quasi-Boolean algebra, if it satisfies hyperidentities of the variety of Boolean algebras. Elementary characterization is proven for quasi-Boolean algebras.
Keywords: quasi-Boolean algebra; hyperidentities